TÉCNICA QUIRÚRGICA DE GASTROYEYUNOSTOMÍA COMO VÍA ALTERNA PARA EL PASAJE DE ALIMENTOS EN PERROS CON ESTENOSIS PILÓRICA EXPERIMENTAL - Mamani P., Víctor (2004)
A surgery technique of gastroyeyunostomy was applied in dogs with experimental pyloric stenosis to observe the transit of chyle through the new path, and to evaluate the adverse effects on the animal. Ten crossbred dogs (5 female and 5 male) of 2-3 years old were surgically pyloric stenosed and the gastroyeyunostomy was performed. Animals were clinically evaluated for 35 days, and then, contrast radiographs were taken before necropsy. The post-surgery clinical observations shown an adequate recovery by day 10 after surgery. Vomit, an important clinical sign was evaluated. Animals were grouped as “bad” for recurrent vomits, “good” for occasional vomits, and “excellent” for animals apparently normal. 33% of dogs were considered as “good” and 67% as “excellent”. An adequate outflow of contrast liquid through the anastomosed organs was observed in all animals. There were no lesions, infections or complications in the abdominal cavity at necropsy. All animals presented gastric biliar regurgitation without serious lesions in the gastric mucosa. Therefore, this technique could be considered simple, useful, with minimal possibilities of iatrogenic trauma.